2020
DOI: 10.1002/mc.23241
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanistic targets of forkhead box Q1 transcription factor in human breast cancer cells

Abstract: The transcription factor forkhead box Q1 (FoxQ1) is overexpressed in different solid tumors including breast cancer, but the mechanism underlying its oncogenic function is still not fully understood. In this study, we compared RNA‐seq data from FoxQ1 overexpressing SUM159 cells with that of empty vector‐transfected control cells to identify novel mechanistic targets of this transcription factor. Analysis of The Cancer Genome Atlas (TCGA) data set revealed significantly higher expression of FoxQ1 in black breas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The study found that FOXQ1 is a direct transcriptional regulator of IL-1α, IL-8 and vascular endothelial growth factor in breast cancer cells (45). FOXQ1 is upregulated in breast cancer tissues, which promotes EMT, cell migration and invasion, self-renewal and metastasis of breast cancer stem cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that FOXQ1 is a direct transcriptional regulator of IL-1α, IL-8 and vascular endothelial growth factor in breast cancer cells (45). FOXQ1 is upregulated in breast cancer tissues, which promotes EMT, cell migration and invasion, self-renewal and metastasis of breast cancer stem cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA‐seq data presented in this study were from our previously published study 14 . The RNA‐seq data was submitted to the Gene Expression Omnibus of NCBI (GSE151059) 14 …”
Section: Methodsmentioning
confidence: 99%
“…The forkhead Box Q1 (FoxQ1) is another transcription factor implicated in the pathogenesis of breast cancer. Overexpression of FoxQ1 has been reported in basal‐like and luminal‐type human breast cancers when compared to normal mammary tissue 13,14 . In breast cancer, the FoxQ1 is best known for its role in promotion of epithelial to mesenchymal transition (EMT) and maintenance of breast cancer stem‐like cells (bCSC) 15–17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations